Moral discourse boosts confidence in moral judgments - Heinzelmann, Nora; Höltgen, Benedikt T. A.; Tran, Viet (Philosophical psychology, 2021)
The so-called “conciliatory” norm in epistemology and meta-ethics requires that an agent, upon encountering peer disagreement with her judgment, lower her confidence about that judgment. But whether agents actually abide by this norm is unclear. Although confidence is excessively researched in the empirical sciences, possible effects of disagreement on confidence have been understudied. Here, we target this lacuna, reporting a study that measured confidence about moral beliefs before and after exposure to moral discourse about a controversial issue. Our findings indicate that participants do not abide by the conciliatory norm. Neither do they conform to a rival “steadfast” norm that demands their confidence to remain the same. Instead, moral discourse seems to boost confidence. Interestingly, we also find a confidence boost for factual beliefs, and a correlation between the extremity of moral views and confidence. One possible explanation of our findings is that when engaging in moral discourse participants become more extreme in their opinions, which leads them to become more confident about them, or vice versa: they become more confident and in turn more extreme. Although our work provides initial evidence for the former mechanism, further research is needed for a better understanding of confidence and moral discourse.